2009
DOI: 10.1002/jmri.21730
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of iron in the hippocampus with MMSE in patients with Alzheimer's disease

Abstract: Purpose: To investigate the brain iron deposits in patients with Alzheimer's disease (AD) and healthy age-matched controls using phase imaging. Materials and Methods:Twenty-six AD patients and 24 healthy controls were recruited. A three-dimensional highresolution, gradient-echo sequence was used to acquire phase data in the coronal plane. A high-pass filter was used to remove the phase variation caused by field inhomogeneity. The regions evaluated included the bilateral putamen, globus pallidus, and the head a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 28 publications
1
67
0
Order By: Relevance
“…Further, the iron transport protein TF functions were also reported to be disrupted in AD (108). AD hippocampus showed a moderate positive correlation with mini-mental state examination (MMSE) scores, and a negative correlation with the duration of the disease for iron using phase imaging (127). A recent study showed that APP protein possesses ferroxidase activity, can catalytically oxidize Fe(2 + ), and has a major interaction with ferroportin.…”
Section: E Role Of Iron In Neurodegenerationmentioning
confidence: 99%
“…Further, the iron transport protein TF functions were also reported to be disrupted in AD (108). AD hippocampus showed a moderate positive correlation with mini-mental state examination (MMSE) scores, and a negative correlation with the duration of the disease for iron using phase imaging (127). A recent study showed that APP protein possesses ferroxidase activity, can catalytically oxidize Fe(2 + ), and has a major interaction with ferroportin.…”
Section: E Role Of Iron In Neurodegenerationmentioning
confidence: 99%
“…Remarkably, recent studies have shown that iron content in brain regions has been positively correlated with poorer performance in cognitive testing in Alzheimer's patients (Ding et al 2009). In addition, redox-active iron levels in the cerebrospinal fluid increased with the degree of cognitive impairment from normal to MCI subjects (Lavados et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Dysfunctional brain iron homeostasis is believed to play an important role in Alzheimer's disease (AD) [3]. Iron accumulation is seen in the AD postmortem brain [4] and iron content correlates with disease duration and Mini-Mental State Examination (MMSE) score [5,6]. Individuals with mild cognitive impairment (MCI) with high risk of AD, showed higher cortical iron in vivo using MRI (measured using quantitative susceptibility mapping techniques), which spatially co-localized with A␤ plaques and correlated with higher plaque load [7].…”
Section: Introductionmentioning
confidence: 99%